Spain, rumor, and anti-Catholicism in mid-Jacobean England : the Palatine match, Cleves, and the Armada scares of 1612-1613 and 1614 /: the Palatine match, Cleves, and the Armada scares of 1612-1613 and 1614. (2019) - Senning, Calvin F
No abstract available